Aircraft-measured indirect cloud effects from biomass burning smoke in the Arctic and subarctic - L. M. Zamora; R. A. Kahn; M. J. Cubison; G. S. Diskin; J. L. Jimenez; Y. Kondo; G. M. McFarquhar; A. Nenes; K. L. Thornhill; A. Wisthaler; A. Zelenyuk; L. D. Ziemba (Atmospheric Chemistry and Physics, 2016)
The incidence of wildfires in the Arctic and subarctic is increasing; in boreal North America, for example, the burned area is expected to increase by 200–300 % over the next 50–100 years, which previous studies suggest could have a large effect on cloud microphysics, lifetime, albedo, and precipitation. However, the interactions between smoke particles and clouds remain poorly quantified due to confounding meteorological influences and remote sensing limitations. Here, we use data from several aircraft campaigns in the Arctic and subarctic to explore cloud microphysics in liquid-phase clouds influenced by biomass burning. Median cloud droplet radii in smoky clouds were ∼ 40–60 % smaller than in background clouds. Based on the relationship between cloud droplet number ( N liq ) and various biomass burning tracers (BB t ) across the multi-campaign data set, we calculated the magnitude of subarctic and Arctic smoke aerosol–cloud interactions (ACIs, where ACI = (1∕3) × d ln ( N liq )∕d ln (BB t )) to be ∼ 0.16 out of a maximum possible value of 0.33 that would be obtained if all aerosols were to nucleate cloud droplets. Interestingly, in a separate subarctic case study with low liquid water content ( ∼ 0.02 g m −3 ) and very high aerosol concentrations (2000–3000 cm −3 ) in the most polluted clouds, the estimated ACI value was only 0.05. In this case, competition for water vapor by the high concentration of cloud condensation nuclei (CCN) strongly limited the formation of droplets and reduced the cloud albedo effect, which highlights the importance of cloud feedbacks across scales. Using our calculated ACI values, we estimate that the smoke-driven cloud albedo effect may decrease local summertime short-wave radiative flux by between 2 and 4 W m −2 or more under some low and homogeneous cloud cover conditions in the subarctic, although the changes should be smaller in high surface albedo regions of the Arctic. We lastly explore evidence suggesting that numerous northern-latitude background Aitken particles can ...